Rasch Analysis of The Indonesian Version of Individual Work Performance Questionnaire (IWPQ) - Weepy Grace Dwiliesanti; Ananta Yudiarso (Fakultas Psikologi UIN Syarif Hidayatullah Jakarta, 2022)
The Individual Work Performance Questionnaire was developed by Koopmans et al. (2013). This questionnaire was based on the construct of individual work performance which consists of task performance, contextual performance, and counterproductive work behavior. Widyastuti & Hidayat (2018) adapted the IWPQ into Bahasa Indonesia. The mentioned research used the classical test theory (CTT) approach to validate the instrument. Therefore, the findings were only applicable to the study’s sample, as validity and reliability could not be legitimately generalized to other study settings. In comparison, the development of the original IWPQ used Rasch analysis to examine its measurement properties. Rasch analysis is a modern psychometric approach based on item response theory (IRT), which has several advantages over the CTT. This study aimed to validate the psychometric properties of the Indonesian Version of IWPQ using the Rasch model. The psychometric properties discussed in this study include instrument reliability, person and item reliability, unidimensionality, rating scale functioning, and bias detection (Differential Item Functioning). The 213 participants in this research survey were Indonesian citizens aged 18-46 years old (mean = 30.64, SD = 8.55) and were actively working for at least three months at their current job. The result showed that the assumption of the unidimensionality of each sub-scale of IWPQ was fulfilled. The 5-Likert rating scales of this instrument had adequate functionality. The person reliability for all sub-scales ranged from .58 - .80. Meanwhile, the item reliability ranged from .90 - .97. The separations were considered high with a value ranging from 3.04 – 5.77. All items in this instrument functioned well to measure individual work performance except for one item in sub-scale Contextual Performance. This specific item should be revised to achieve a more accurate measurement of the construct. There was one item that was considered biased toward gender in sub-scale Contextual Performance. Also, there was one item that was considered biased toward tenure in sub-scale Counterproductive Work Behavior. These findings had implications for using the Indonesian Version of IWPQ to assess employees’ individual work performance and recommendations for future research.